Improved methods for the construction of relative invariants for permutation groups. (March 2017) - Elsenhans, Andreas-Stephan
Abstract: An invariant of a group U is called a relative invariant of U ⊊ G if its stabilizer in G is U . The computation of Galois groups requires the construction of such invariants for permutation groups. This article reports on the constructions that are implemented in the Galois group package ofmagma 2.20.